A study to assess awareness on disaster management among school going children in Gwalior (M.P.) - Marskole, Priyesh; Mishra, Ashok; Kumar, Prakhar; Gaur, Pradeep; Aharwar, Poornima; Patidar, Pragya; Shejwar, Pragati (International Journal Of Community Medicine And Public Health, 2018)
Background: The classical characterization of disaster is unfamiliarity, unpredictability, uncertainty, vulnerability, urgency, intensity and danger. Major disasters include earthquake, landslides, volcanic eruptions, floods hurricanes, fires, tornados, blizzards, tsunamis, cyclones. Apart from causing deaths and severe ill health, disasters also lead to large scale displacement, injuries, epidemics and substantial economic losses to the communities. Though every emergency or disaster has it’s own characteristics and demands but the basic measures under disaster management include prevention, mitigation, preparedness, response and recovery for which regular training and awareness activities are needed especially among students. The objective of the study was to assess the extent of awareness about disasters and their management among school going children. Methods: It was an educational interventional design with an exploratory research approach adopting non- probability purposive sampling technique. Kendriya vidhyalaya no: 4 affiliated to CBSE was randomly selected, which is situated in mid of the Gwalior town. Survey method was employed, on 110 participants aged between 12 and 16 years using a pre-tested semi structured questionnaire data sheet. Results: The outcome revealed that out of 110 students 87.2% (before intervention) and 98.2% (after intervention) had knowledge of disaster management. Conclusions: These findings emphasize that the extent of knowledge is not yet satisfactory and there is a severe need of providing knowledge to the school children. Disaster management can be compulsorily included in academic curriculum of all the students. Effective, purposeful training and awareness programmes are to be timely conducted.